Pemikiran Neal Robinson: Kronologi Turunnya al-Qur’an - Alfiyah, Avif; Umah, Khurul Aimmatul (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
One of the Orientalist figures in the world of interpretation is Neal Robinson. This paper explored the idea of Neal Robinson in his book, Discovering The Qur'an: A Contemporary Approach To A Veiled Text in order to understand the chronology of surah in the Qur'an. The aim of this research is to find out and understand Neal Robinson's thoughts on the chronology of the revelation of the Koran, which in this case is divided into three types. The method we use in this paper is the hermeneutical method. After reading the book, the writer found that there are three strategies to understand the chronology of the surah in the Qur'an; They are investigating the events of occasions of the revelation (asbab an-nuzul), understanding the literature of abrogating and abrogated ayahs (nasikh and mansukh), and categorizing the traditional lists of Meccan and Madinan surahs (Makiyyah and Madaniyyah). By conducting those ways, Robinson proved that asbab an-nuzul should be treated with extreme caution. Then, in some cases, asbab an-nuzul should be limited in order to determine the chronological order of the Qur’an. After that, nasikh and mansukh are used merely for the purpose of determining the chronological order of the Qur’an and did not highlight certain evolution within a period of revelation. Finally, by analyzing Madaniyah and Makiyah surah, it revealed the certainty of the origin and the list of traditional surah in which there were some differences in the determination of the date among the companions. The differences are due to rivalry in the collection of the Qur'an and wrong isnads done by some componions in order to increase their prestige